2018
DOI: 10.1136/sextrans-2018-053619
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccine uptake among young gay and bisexual men who have sex with men with a time-limited targeted vaccination programme through sexual health clinics in Melbourne in 2017

Abstract: ObjectiveIn mid-2017, the Victorian Government funded a free time-limited human papillomavirus (HPV) vaccination catch-up programme for gay and bisexual men who have sex with men (MSM) aged up to 26 years through sexual health clinics or other immunisation centres. We aimed to examine the uptake of the HPV vaccine among young MSM attending the Melbourne Sexual Health Centre (MSHC).MethodsMSM aged ≤26 attending MSHC between 27 April 2017 and 31 December 2017 were included in the analysis. HPV vaccine uptake was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Higher uptake may also be due to more regular contact with service, as men on PrEP return regularly for HIV/STI check-ups. A previous study also demonstrated that MSM taking PrEP were more likely to receive HPV vaccine than MSM who did not take PrEP 10. In addition, men who had a higher number of male partners are at higher risk of acquiring HAV, and our findings indicate that this group were more likely to receive the hepatitis A vaccine which will aid in preventing future outbreaks through their sexual networks.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Higher uptake may also be due to more regular contact with service, as men on PrEP return regularly for HIV/STI check-ups. A previous study also demonstrated that MSM taking PrEP were more likely to receive HPV vaccine than MSM who did not take PrEP 10. In addition, men who had a higher number of male partners are at higher risk of acquiring HAV, and our findings indicate that this group were more likely to receive the hepatitis A vaccine which will aid in preventing future outbreaks through their sexual networks.…”
Section: Discussionsupporting
confidence: 71%
“…All MSM in Victoria were eligible for the two-dose course of hepatitis A vaccine (Havrix 1440; GlaxoSmithKline), with the second dose given 6–12 months after the first dose 7. At the same time, the Victorian DHHS began to offer free meningococcal ACWY (Menactra; Sanofi) and human papillomavirus (HPV) (Gardasil; Merck & Co.) vaccines for eligible MSM, while an existing hepatitis B vaccination programme continued 7 10. The ‘Little Pricks’ campaign was launched in 2018 to increase the uptake of all four vaccines in MSM in Victoria, which was run by the Victorian DHHS in partnership with a community-based organisation Thorne Harbour Health (formerly Victorian AIDS Council).…”
Section: Introductionmentioning
confidence: 99%
“…Our observation that MSM with more partners were more likely to receive the MenACWY vaccine fits with previous observations at our clinic with the HPV and hepatitis A vaccine, suggesting this core group is protected against the infection within wider sexual networks to prevent ongoing transmission 26 27. Our data show that MSM who have both male and female partners were less likely to receive the MenACWY vaccine, which was consistent with the HPV vaccine uptake 26. It is possible that men who have sex with men and women may consider themselves to have a lower risk of acquiring IMD compared with men who have sex with men only, but further research will be required to confirm this.…”
Section: Discussionsupporting
confidence: 90%
“…During the same time period, two other vaccines (ie, human papillomavirus (HPV) and hepatitis A) were also provided for free to eligible MSM as part of the government-funded vaccination programme in Victoria 26 27. Our observation that MSM with more partners were more likely to receive the MenACWY vaccine fits with previous observations at our clinic with the HPV and hepatitis A vaccine, suggesting this core group is protected against the infection within wider sexual networks to prevent ongoing transmission 26 27. Our data show that MSM who have both male and female partners were less likely to receive the MenACWY vaccine, which was consistent with the HPV vaccine uptake 26.…”
Section: Discussionsupporting
confidence: 89%
“…8 Therefore, MSM who are not eligible for the school-based vaccination programme have to pay for the vaccination. In mid-2017, the Victorian State Government introduced a free time-limited targeted HPV vaccination programme for MSM aged up to 26 years, 9 and it is estimated that about 43% of unvaccinated MSM aged 20–26 years had any quadrivalent vaccine-preventable genotypes detected at the anus before receiving the first dose of the HPV vaccine. 10…”
Section: Introductionmentioning
confidence: 99%